Etika Salib dalam Filipi 2:5-11; Formasi Spiritual Jemaat dalam Perspektif Kristologi Paulus - Marga Diraja; Nik Anna; Adi Prasetyo Wibowo (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Contemporary congregational spirituality faces significant challenges due to the rise of individualism, competition, and self-centered orientations that hinder the practice of humility, service, and unity among believers. This condition highlights the importance of a strong theological foundation for cultivating Christ-centered spirituality. This study aims to examine the concept of the ethics of the cross in Philippians 2:5–11 from the perspective of Pauline Christology, identify the ethical values embedded within the passage, and explain their implications for congregational spiritual formation. The study employs a qualitative method with a theological-expository approach through library research and exegetical analysis of Philippians 2:5–11. The findings reveal that the ethics of the cross is rooted in Christ’s self-emptying, His taking the form of a servant, His obedience unto death on the cross, and His subsequent exaltation by God. This ethical framework is expressed through three principal values: relinquishing personal rights and privileges, serving with humility, and demonstrating complete obedience to the will of God. The findings further indicate that congregational spiritual formation should be centered on the transformation of the mind, a life characterized by service, and communal relationships that reflect the character of Christ. The novelty of this study lies in its formulation of the ethics of the cross as a systematic and Christ-centered model of spiritual formation that bridges Pauline Christology and the spiritual development of contemporary congregations.